Water surface tension modulates the swarming mechanics of Bacillus subtilis - Ke, Wan-Ju; Hsueh, Yi-Huang; Cheng, Yu-Chieh; Wu, Chih-Ching; Liu, Shih-Tung (Frontiers in Microbiology, 2015)
Many Bacillus subtilis strains swarm, often forming colonies with tendrils on agar medium. It is known that B. subtilis swarming requires flagella and a biosurfactant, surfactin; and in this study, we find that water surface tension plays a role in swarming dynamics. B. subtilis is shown to extract water from the agar to fill their colonies, and when a low amount of surfactin is produced, the water surface tension of the colony restricts expansion, causing bacterial density to rise. The increased density induces a quorum sensing response that leads to heightened production of surfactin, which then weakens water surface tension to allow colony expansion. When the barrier formed by water surface tension is breached at a specific location, a stream of bacteria swarms out of the colony to form a tendril. If a B. subtilis strain produces surfactin at levels that can substantially weaken the overall water surface tension of the colony, water floods the agar surface in a thin layer, within which bacteria swarm and migrate rapidly. This study sheds light on the role of water surface tension in regulating B. subtilis swarming, and provides an explanation for the mechanisms underlying swarming initiation and tendril formation.